Understanding Complex Roles of Family for Latina Health: Evaluating Family Obligation Stress - Molina, Yamile (Fam Community Health, 2019)
We developed a measure of family obligation stress and compared its relationship to health and unmet healthcare needs relative to social support among a sample of US-based Latinas. Data come from a randomized controlled trial within four clinics to increase mammography among Latinas (N = 539). The 1-factor measure had acceptable reliability and construct validity. Family obligation stress was associated with worse health and greater unmet healthcare needs. Family obligation stress varied by years in the US and country of origin. Our measure of family obligation stress contributes new venues to family research among Latino populations.